Puujee - Yamada, Kazuya (Japan, 2007)
Verzio FF submission On a long trek photographing individuals of many countries, photographer Yoshiharu Sekino happens upon a family in Mongolia. They immediately capture his imagination and become subjects in a photo essay he publishes, but he also forms an ongoing friendship with them. The film depicts their initial encounter and the events of the next five years as Sekino goes away and comes back repeatedly, witnessing changes with each return. At the center of this moving group portrait is the captivating figure of Puujee, a young girl who becomes the film’s pivotal character, and whose destiny seems tied to the hundreds of thousands of agrarian Mongolians who have moved to cities to escape deprivation and the deleterious effects of the new market economy. Already adept at herding animals on horseback, six-year-old Puujee defies Sekino and his omnipresent camera, even though her family members welcome him. Gradually allowing Sekino into her trust, she shares her dream of becoming a teacher. When she finally gets her chance to enter school, the gulf between Puujee and her family yawns ever wider, evident in her rebelliousness and alienation.